Exploring Macrophage-Dependent Wound Regeneration During Mycobacterial Infection in Zebrafish - Bohaud, Candice; Johansen, Matt D.; Varga, Béla; Contreras-Lopez, Rafael; Barthelaix, Audrey; Hamela, Claire; Sapède, Dora; Cloitre, Thierry; Gergely, Csilla; Jorgensen, Christian; Kremer, Laurent; Djouad, Farida (Frontiers in Immunology, 2022)
The molecular and cellular mechanisms associated with tissue degradation or regeneration in an infectious context are poorly defined. Herein, we explored the role of macrophages in orchestrating either tissue regeneration or degradation in zebrafish embryos pre-infected with fish pathogen Mycobacterium marinum. Zebrafish were inoculated with different infectious doses of M. marinum prior to fin resection. While mild infection accelerated fin regeneration, moderate or severe infection delayed this process by reducing blastemal cell proliferation and impeding tissue morphogenesis. This was correlated with impaired macrophage recruitment at the wound of the larvae receiving high infectious doses. Macrophage activation characterized, in part, by a high expression level of tnfa was exacerbated in severely infected fish during the early phase of the regeneration process, leading to macrophage necrosis and their complete absence in the later phase. Our results demonstrate how a mycobacterial infection influences the macrophage response and tissue regenerative processes.